2021
DOI: 10.1177/17588359211053416
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in breast cancer patients: a subanalysis of the OnCovid registry

Abstract: Background: Cancer patients are at higher risk of COVID-19 complications and mortality than the rest of the population. Breast cancer patients seem to have better prognosis when infected by SARS-CoV-2 than other cancer patients. Methods: We report a subanalysis of the OnCovid study providing more detailed information in the breast cancer population. Results: We included 495 breast cancer patients with a SARS-CoV-2 infection. Mean age was 62.6 years; 31.5% presented more than one comorbidity. The most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…An explanation for the lower mortality rate in BC patients would be the existence of some level of hormonal protection, especially estrogen. Therefore, in the study conducted by Garrigós et al, 2021, that suggested this association, the authors observed that mortality rates from COVID-19 were slightly lower in BC patients (11%) than in those women diagnosed with other types of genitourinary cancer (14%). Based on these results, we have included here a complementary analysis comparing the mortality rate between BC and GC patients younger (18 to 49 years) and those aged 50 years and over.…”
Section: Discussionmentioning
confidence: 96%
“…An explanation for the lower mortality rate in BC patients would be the existence of some level of hormonal protection, especially estrogen. Therefore, in the study conducted by Garrigós et al, 2021, that suggested this association, the authors observed that mortality rates from COVID-19 were slightly lower in BC patients (11%) than in those women diagnosed with other types of genitourinary cancer (14%). Based on these results, we have included here a complementary analysis comparing the mortality rate between BC and GC patients younger (18 to 49 years) and those aged 50 years and over.…”
Section: Discussionmentioning
confidence: 96%
“…The hospitals had no choice but either delay cancer surgeries or transition to the ambulatory surgery with telemedicine follow‐up 11 . This change was driven by the common goal to preserve resource for COVID‐19 positive patients without compromising long‐term outcomes for breast cancer patients 10,12,13 …”
Section: Discussionmentioning
confidence: 99%
“…11 This change was driven by the common goal to preserve resource for COVID-19 positive patients without compromising long-term outcomes for breast cancer patients. 10,12,13 One of the practice-changing recommendations that emerged during the pandemic was an increased use of Enhanced Recovery After Surgery (ERAS) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the putative detrimental effect of recent exposure to active anticancer therapy before the infection appears to be attenuated in this patient population. 12…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the putative detrimental effect of recent exposure to active anticancer therapy before the infection appears to be attenuated in this patient population. 12 Outcomes from COVID-19 in patients with cancer have also considerably evolved over time. Enhanced health care system capacity and improved management of COVID-19, 13 widespread immunization campaigns, 14 shifting changes in community transmission, and the emergence of new SARS-CoV-2 variants 15 have dramatically changed the clinical impact of SARS-CoV-2 infection since declaration of the pandemic in March 2020.…”
Section: Introductionmentioning
confidence: 99%